Development of a Digital Payment-Based Order Information System at the Baker Old Asem Baris Outlet - Mohamad Rakan; Cholid Mawardi; Yudha Pradana (International Journal Labs, 2026)
The rapid development of digital technology has encouraged small and medium-sized enterprises (SMEs), particularly culinary businesses, to adopt information systems to improve operational efficiency, transaction accuracy, and customer service quality. Baker Old Asem Baris Outlet still relied on conventional ordering and payment processes, which resulted in several operational challenges, including slow order processing, transaction recording errors, data duplication, and increased employee workload. This research aimed to develop a digital payment-based ordering information system that integrated online ordering, electronic payment, transaction management, and sales reporting features to support business digital transformation. This study employed a Research and Development (R&D) approach using the Waterfall software development model, which consisted of requirement analysis, system design, implementation, testing, and maintenance stages. The system was developed using the CodeIgniter framework, a MySQL database, and digital payment integration through a payment gateway. The results showed that the developed system successfully provided product catalog management, online ordering facilities, digital payment services, administrative dashboards, and automated sales reporting features. Functional testing using the black-box testing method demonstrated that all system features operated according to the expected specifications. Furthermore, usability evaluation using the System Usability Scale (SUS), involving 25 respondents, obtained an average score of 78.2, which was categorized as good and acceptable. The study concluded that the developed digital payment-based ordering information system effectively improved transaction efficiency, reduced manual errors, and supported the operational management of Baker Old Asem Baris Outlet. This research contributed to the implementation of practical digital solutions for culinary SMEs in adapting to the digital economy.